Karakteristik Mutu Sambal Ikan Sagela Asap Yang Dipasarkan Di Kota Gorontalo - Humalangi, Siti Marwah; Sulistijowati, Rieny; Husain, Rahim; Tumanduk, Nova (Politeknik Kelautan dan Perikanan Bitung, 2023)
The smoked sagela fish sauce is a specialty product of Gorontalo and is widely marketed as a souvenir. However, chilli sauce is also often contaminated by chemical and biological contaminants. Biological contaminants include coliform and mold. This research aims to analyze the quality characteristics of sagela fish chilli sauce which was marketed in Gorontalo City. The method used in their research was a quantitative descriptive method. The procedure of research was observing shops and taking samples from three shops selling sagela fish chilli sauce souvenirs, namely shops X, Y and Z. The test parameters were coliform, mold, pH and dissolved solids. The data analysis design used tables, then the frequency distribution is accompanied by an explanation of the table. The test results for Coliform bacteria in a range of requirements ranged from a Z shop ranging at a value of <3 MPN/g. The results of the mold test that met the requirements were found in shop Y at a value of 10 – 40 CFU/g. The results of the pH test for all meet requirements from ranging 5.34 to 5.86. The dissolved solids test results that met the requirements were samples from store X with a value of 17.39 % b/b. All test results have been compared to chili sauce SNI No. 01-2976-2006